Vascular Disease in Young Indians (20-40 years): Role of Ischemic Heart Disease - Dalal, Jamshed (J Clin Diagn Res, 2016)
Coronary Artery Disease (CAD) occurs at a younger age in Indians with over 50% of Cardiovascular Disease (CVD) mortality occurring in individuals aged less than 50 years. Although several risk factors have been suggested; smoking, dyslipidemia and hypertension are major risk factors in the young. In this review, we have pooled the current evidence on Ischemic Heart Disease (IHD) in young (20-40 years) and provided an opinion for the effective management of IHD in young Indians.